Sam, the sea cow - Jacobs, Francine; Kelly, Laura (New York : Walker, 1992)
Follows the adventures of a manatee, or sea cow, from birth till after he leaves his mother.
Originally published: Sewer Sam, the sea cow. New York : Walker, 1979.
3.6
K-3
Keywords: Manatees -- Juvenile literature; Manatees; Manatees